1984
DOI: 10.1007/bf00213740
|View full text |Cite
|
Sign up to set email alerts
|

Age-related decline of lymphoid-tissue components in the oral mucosa of the lip, cheek and soft palate of Macaca fascicularis

Abstract: In three mature monkeys (Macaca fascicularis; 3.5 +/- 0.3 kg in weight), the labial, buccal and soft-palate mucosae were examined morphologically and stereologically. Using fixation by perfusion, standardized methods of tissue preparation and morphometric analysis at the light-microscopic level, the gross dimensions (i.e., epithelial thickness, width of combined lamina propria/submucosa) and the volumetric composition of the oral mucosae were estimated and compared with those of young animals examined previous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

1985
1985
1988
1988

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 7 publications
1
1
0
Order By: Relevance
“…The periductal lymphocytic foci that were identified in the sublingual glands in this study may represent normal periductal lymphoid tissue similar to that described in monkeys [Schroeder & Dorig-Schwarzenbach, 1984]. By contrast, in monkeys the quantity of lymphoid tissue is reported to decline with age while the frequency of foci increased with age in this study.…”
Section: Discussionsupporting
confidence: 81%
“…The periductal lymphocytic foci that were identified in the sublingual glands in this study may represent normal periductal lymphoid tissue similar to that described in monkeys [Schroeder & Dorig-Schwarzenbach, 1984]. By contrast, in monkeys the quantity of lymphoid tissue is reported to decline with age while the frequency of foci increased with age in this study.…”
Section: Discussionsupporting
confidence: 81%
“…Nevertheless, in a recent study using M. /afscicu/ariis animals of approximately known age. Schroeder and Dorig-Schwarzenbach (1984) reported an age-related decline of DALT in young vetrsits mature animals. Averaged data of this study fit well into the curves over age, found in the present study (Figs.…”
Section: Resultsmentioning
confidence: 96%